1998
DOI: 10.1080/02626669809492135
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of annual streamflow and the Southern Oscillation in Costa Rica

Abstract: This study illustrates the association between annual and seasonal streamflow characteristics on six Costa Rican rivers and the Southern Oscillation Index (SOI). Annual discharge from rivers within the Pacific watershed are clearly positively associated with contemporary values of the SOI and experience significant reductions in both mean and variance in El Nine years. The considerable practical implications of this finding to a country in which over 60% of national electrical power comes from hydroelectric sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…A recent regional analysis of 18 rivers located throughout New Zealand (Mosley, 2000), highlighted the potential for considerable regional diversity in the individual response of rivers to the ENSO. Similar variability was observed by George et al (1998) for six rivers in Costa Rica, with elevation being observed as a contributing factor governing the association of the ENSO to hydrological response. At the even finer regional-catchment scale little work has been documented.…”
Section: Introductionsupporting
confidence: 49%
“…A recent regional analysis of 18 rivers located throughout New Zealand (Mosley, 2000), highlighted the potential for considerable regional diversity in the individual response of rivers to the ENSO. Similar variability was observed by George et al (1998) for six rivers in Costa Rica, with elevation being observed as a contributing factor governing the association of the ENSO to hydrological response. At the even finer regional-catchment scale little work has been documented.…”
Section: Introductionsupporting
confidence: 49%
“…Figure 1 reveals stations in all regions of Costa Rica, with the exception of the extreme northeast and east central regions, and a strong bias towards the populated Central Valley. Following the definition of the Veranillos and Caniculas in this region (Hastenrath, 1967, , 1950-1999 (lower). 1975; George et al, 1998, andMagaña et al, 1999), July and August rainfalls are summed to create a single seasonal total. For the sake of simplicity and to maximize the size of the available data sets, each set is subdivided into four categories dependent upon the SST anomalies (positive or negative) in the two oceans in the corresponding season.…”
Section: Datamentioning
confidence: 99%
“…A reduction in the drought increases the risk of flooding in the subsequent months of heavy rains. George et al (1998) also indicate a reciprocal relationship to rainfall and flooding within the Caribbean drainage of Costa Rica. Monthly precipitation and flood risks during this period in Costa Rica have been shown to be associated with the El Niño-Southern Oscillation (ENSO) phenomenon (Waylen et al, 1996;Waylen and Laporte, 1999), however that association is not as strong as has been found in many similar tropical regions (Ropelewski and Halpert, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological models can provide such information, but traditional calibration techniques require hydrological data, which often are of low quality and/or not available in many regions worldwide, such as Central America. On the other hand, climate variability exerts a strong influence on streamflow variability on long and short timescales, particularly in the Central American region—where it frequently causes droughts and floods with many negative consequences (Alfaro & Pérez‐Briceño, ; George, Waylen, & Laporte, ). Furthermore, there is a good knowledge about this variability, commonly expressed in terms of variations in precipitation at intra‐annual and interannual timescales.…”
Section: Introductionmentioning
confidence: 99%